Anatomical Variations in Aortic Arch Branching Pattern: A Computed Tomography Scan Study in Nepalese Population - Makaju, Sarbada; Chaudhary, Sonam; Chaudhary, Arbvind; Kala Rai, Chandra; Shrestha, Samip (Nepal Journal of Medical Sciences, 2025)
Introduction: The aortic arches consist of three main branches. And these branches supply the upper limb, head, neck and brain. The knowledge of these anatomical variations is significant for diagnostic, surgical, and interventional surgeries of the thorax and neck. Thus, this study aims to know the anatomical variation in the branching patterns of aortic arches among Nepalese population. Methods: This descriptive study was carried out in the Department of Radiology of KMCTH between 15 November 2024 to 16 February 2025 after getting the ethical clearance from the Institutional Review Committee (reference no. KMC-IRC 16102024/03). The total collection in these three months was 200 after taking the consent verbally. The Convenient sampling was done. The study was done in CT scan contrast. In this, the variation of the aortic arches were studied under the different types I- Types VII. The data was analyzed with Statistical Package for the Social Sciences 20 version. Results: In this study, the maximum distribution of sample was between 56-65 years and 108 (54%) were male and 92 (46%) were female and the most common variation of the aortic arches were the normal i.e aortic arches giving rise to the three main branches. However, it was followed by type II aortic arch second common among distribution in both genders. In this study the type III and Type IV was seen in both the gender. But there is no data in TypeV-TypeVII. Conclusions: The variation in the branches of aorta is crucial in emergency during cardiothoracic surgery. The identification of variation may achieve desired objectives and avoid complications during vascular and intervention surgery.